Optimizing Fabric Storage using Dedicated Storage for Order Picking Efficiency: Arena Simulation at PT. ABC - Nazariah, Putri Ridha Maulia; Taqwali, Ega; Okitasari, Hanissa (Journal of Advances in Information and Industrial Technology, 2024)
Order picking is a crucial process in warehouse management, where efficiency in retrieving items significantly impacts operational smoothness and the company's ability to meet product demand on time. PT ABC is a garment company that faces issues with order-picking activities in the fabric material warehouse. The material search process, which takes up to 70 minutes, is caused by an inefficient random storage system. This study aims to optimize material storage using the dedicated storage method and simulation with Arena software. With this approach, storage allocation based on buyers is implemented to improve the efficiency of material retrieval time. The simulation results indicate a reduction in material search time to 41.86 minutes, improving efficiency by 40.2%. The dedicated storage method has proven effective in enhancing warehouse operational efficiency, enabling the company to reduce material search time.